Endoscopic Carpal Tunnel Release using a modified application technique of local anesthesia: safety and effectiveness - Nabhan, Abdullah; Ishak, Basem; Al-Khayat, Jehad; Steudel, Wolf-Ingo (Journal of Brachial Plexus and Peripheral Nerve Injury, 2008)
Background Local anesthesia is widely used for open carpal tunnel release. However, injection of local anesthesia as described by Altissimi and Mancini (1988) can interfere with endoscopic carpal tunnel release, by increasing the bulk of synovial layers and consequently result in worsening of the view.Purpose The purpose of this study was to evaluate the safety, efficacy using modified technique for application of local anesthesia.Methods 33 patients suffering from gradual increasing symptoms of carpal tunnel syndrome. The patients were also asked to evaluate the pain associated with injection as well as tourniquet during surgery using Visual Analogue Scale (VAS) (ranging from 0 = no pain to 10 = maximum pain).Results One patient required additionally local anesthesia because of mild pain in the hand. The tourniquet was inflated for 13.00 (2.8 min). The pain score related to injection was 2.5 (0.8) and to tourniquet was 3.6 (0.9). Inflation of the tourniquet was well tolerated by all patients. Postoperative neurological sensory and motor deficits related to surgery and local blocks were not occurred.Conclusion Endoscopic release of the carpal tunnel syndrome in local anesthesia is effective, well tolerated and safe. This kind of application of local anesthesia did not reduce visibility.